1984
DOI: 10.1111/j.1432-1033.1984.tb08022.x
|View full text |Cite
|
Sign up to set email alerts
|

Isolation of a novel antibody, which precipitates ribonucleoprotein complex containing threonine tRNA from a patient with polymyositis

Abstract: We have isolated and characterized a novel antibody from a patient with polymyositis, which precipitates threonine tRNA and an unknown small RNA molecule from 32P‐labeled HeLa extract. Fingerprint analysis showed that the human threonine tRNA precipitated was nearly identical to the murine tRNA described by Harada [(1978) Seikagaku 50, 397–411]. Nucleotide analysis suggested that the other small RNA molecule might be transfer RNA. Since phenol extraction resulted in the loss of immunoprecipitability, the prote… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
5
0
1

Year Published

1985
1985
1995
1995

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 31 publications
(6 citation statements)
references
References 16 publications
0
5
0
1
Order By: Relevance
“…The reactive antigens are usually tRNA-associated proteins; in only a few cases are they the tRNAs themselves (4,6). Some of these protein antigens have been identified as aminoacyl-tRNA synthetases (3,(6)(7)(8)(9)(10).…”
mentioning
confidence: 99%
See 1 more Smart Citation
“…The reactive antigens are usually tRNA-associated proteins; in only a few cases are they the tRNAs themselves (4,6). Some of these protein antigens have been identified as aminoacyl-tRNA synthetases (3,(6)(7)(8)(9)(10).…”
mentioning
confidence: 99%
“…All values are for 1:10 serum dilutions; cpm is the amount of radioactivity converted to trichloroacetic acid-precipitable form. The positive control sera [anti-isoleucyl-tRNA synthetase (10), anti-PL-7 (anti-threonyl-tRNA synthetase) (8,9), and anti-Jol (anti-histidyl-tRNA synthetase) (3)] are specific for their particular synthetases.…”
mentioning
confidence: 99%
“…2, specific immunoprecipitation of tRNA by KJ serum could not be demonstrated. Previous studies have consistently found that autoantibodies to any of the five antigenic aminoacyl-tRNA synthetases immunoprecipitate their respective cognate tRNAs (4,(22)(23)(24)(25)32). This is demonstrated in Fig.…”
Section: Resultsmentioning
confidence: 99%
“…There is a distinct enzyme in the cytoplasm for each amino acid (as well as a second in the mitochondria). Antibodies to two of the other aminoacyl-tRNA synthetases have been reported in myositis patients, anti-threonyl-tRNA synthetase (anti-PL-7) (22,23) and anti-alanyl-tRNA synthetase (anti-PL-12) (24). Although exceptions occurred, almost all the patients in whom these antibodies were found had myositis (9,22,24), and most also had ILD (9).…”
mentioning
confidence: 98%
“…During the last three decades it turned out that some diseases which are classically categorized as rheumatic diseases are connected with formation of antibodies against nucleic acids (Okada et al, 1984) and proteins of the own organism (Marguerie etal., 1990;Sontheimer et al, 1992). Among the diverse species of autoantibodies a few immunogobulins were detected which reacted with aminoacyl-tRNA synthetases.…”
Section: Threonyl-trna Synthetase and Autoimmune Diseasesmentioning
confidence: 99%